Peningkatan Kualitas Produksi Keripik Umbi-Umbian Menggunakan Alat Pengering Buatan - Muhammad Firmansyah; Arfida Boedirochminarni (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2025)
This community service activity aims to provide solutions for partners who have problems and experience difficulties in drying tuber chips during cloudy/rainy weather. The activity implementation team designed a dryer (spinner) to help the drying process despite insufficient sunlight. Using a dryer (spinner) has been proven to increase the productivity of tuber chips by around 200% during cloudy or rainy weather compared to drying without a spinner. This dryer (spinner) uses low-power electricity (300 watts). It is designed with fairly simple technology so that partners can easily operate it and use it in subsequent community service activities.